SUPERVISI AKADEMIK BERBASIS COACHING DALAM MENINGKATKAN MUTU PEMAHAMAN KURIKULUM MERDEKA BELAJAR DENGAN PENDEKATAN DEEP LEARNING - Desy Aria Qurotul A’yun; Mukhammad Ishomuddin; Addin Arsyadana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of improving learning quality through understanding a deep learning-based curriculum that emphasizes meaningful learning, critical thinking, and knowledge integration. The purpose of this study is to analyze the implementation of coaching-based academic supervision in improving teachers’ understanding of the deep learning curriculum at MA Nurul Faizah Pasuruan. This study uses a qualitative approach with data collection techniques including interviews, observations, and documentation. The research subjects are the principal and teachers. Data analysis is conducted through data reduction, data display, and conclusion drawing with triangulation to ensure validity. The results show that coaching-based academic supervision is implemented through a dialogic, reflective, and collaborative approach involving goal setting, understanding real conditions, exploring solutions, and commitment to action. This approach enhances teachers’ understanding of deep learning concepts, encourages reflection, and improves teaching practices continuously. Despite challenges such as limited time and workload, this approach remains effective in fostering a professional and adaptive learning culture oriented toward improving educational quality.